Adsorption of Erlotinib to Multiwalled Carbon Nanotubes (2016)
ABSTRACT: Objective: The objective of this research was to assess for the first time the adsorption of erlotinib (ERL) in three types of multi walled carbon nanotubes, as feasible alternative method to removal antineoplastic from wastewater. Methods: Both multi walled carbon nanotubes without modification (pristine-CNT) and modified carbon nanotubes by oxidation (CNT-COOH) and amination (CNT-NH2 Results: The characterization showed that the surface of pristine-CNT was modified. Different sedimentation behavior was observed in the three types of CNTs. ERL adsorption followed the Langmuir model for CNT-NH) were used as adsorbents. They were characterized by Transmission electron microscopy, Raman spectroscopy, FT-IR spectroscopy, and Thermogravimetric analysis. In addition, the stability of CNTs suspensions were monitored. The ERL residual concentration in the equilibrium, from the bath adsorption, experiments was quantified by HPLC. The experiment data were fitted to Langmuir and Freundlich models. Conclusion: It was found that CNTs have a high capacity of adsorption of ERL, indicating the potential of CNTs to removal this antineoplastic drug from hospital wastewater.